Analysis of Factors in Pregnant Women on the Incidence of Preeclampsia - Anjelina Puspita Sari; Romlah Romlah; Titin Dewi Sartika Silaban (GLOBAL HEALTH SCIENCE GROUP, 2024)
Preeclampsia in Indonesia is still the largest part of the problem that contributes to maternal and fetal deaths worldwide recorded in Indonesia as many as 1,077 cases. Objective: This study aims to see what factors have a chance of increasing the incidence of preeclampsia. Method: The type of research uses quantitative analytical research with a cross sectional design. The study was conducted in the city of Palembang on 86 samples using secondary data which was then analyzed to determine the relationship between factors and the incidence of preeclampsia. the research implementation is February-April 2024. Results: he results of the statistical test of logistic regression of bivariate results showed that it was significantly related to age (0.000), education level (0.042), gravida status (0.000), hemoglobin (0.002), nutritional status (0.016), history of hypertension (0.000), history of diabetes mellitus (DM) (0.008), calcium consumption (0.003). Conclusions: Based on the results of the multivariate test, there is a variable that is most closely related to the incidence of preeclampsia is age (0.000). Advice according to the results of the research midwife can control maternal factors and screen when patients are planning a pregnancy.